Students' Written Communication Skills in Science Learning - Annisa Al Fatihah; Y Yennita; Dedi Futra (Yayasan Keluarga Guru Mandiri, 2022)
Communication skills are one of the skills needed by humans in the 21st century. Mathematical communication skills are very important for every student to have, this is useful so that students can understand the problems in science learning given and students are able to express their ideas in solving these problems. This study aims to describe the level of students' written communication skills in science learning. The type of research used is survey research. The sample of this research was 53 respondents of class VIII MTsN 4 Bengkalis. Data collection were techniques in the form of giving a test totaling 10 questions. The questions used refer to 4 aspects of communication skills, namely, 1) Changing the form of data presentation, 2) The accuracy of the use of notation, vocabulary, sketches, graphs, tables, and pictures, 3) The suitability of writing problem-solving steps, 4) Making conclusions. The average percentage of students' written communication skills for each aspect and each indicator is; 1) 72,96 for indicators changing the presentation of data, 2) 44,03 for indicators using graphs, tables, and diagrams, 3) 24,29 for indicators explaining events or experimental results and 4) 47,88 for concluding. In all aspects of written communication, the average score obtained is 47.29, which is included in the poor category.